2012
DOI: 10.1371/journal.pone.0048923
|View full text |Cite
|
Sign up to set email alerts
|

Appraising Hospital Performance by Using the JCHAO/CMS Quality Measures in Southern Italy

Abstract: ObjectivesThe main objective of the present study was to estimate the uptake to quality indicators that reflect the current evidence-based recommendations and guidelines.MethodsA retrospective review of medical records of patients admitted to two hospitals in the South of Italy was conducted. For the purposes of the analysis, a sets of quality indicators has been used from the Joint Commission on Accreditation of Hospital Organizations and Centers for Medicare & Medicaid Services. Four areas of care were selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 36 publications
3
7
1
Order By: Relevance
“…In conclusion, our findings revealed significant deficiencies in the adherence to recommended processes of perinatal care and, consistently with previous studies conducted by some of us to estimate the adherence to evidence-based processes of care in several settings [7,44,45], suggest that it is essential to increase efforts to implement evaluation processes that reflect the healthcare quality based on current evidence and related practice guidelines. The application of the JCAHO PC indicators has demonstrated to be feasible, intuitive and useful to measure perinatal hospital performance, and, although the poor comparability among multiple available quality measures represents a barrier, these performance metrics can be reliably used within an institution, thus enabling comparisons of performance over time, particularly after the implementation of quality improvement interventions.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In conclusion, our findings revealed significant deficiencies in the adherence to recommended processes of perinatal care and, consistently with previous studies conducted by some of us to estimate the adherence to evidence-based processes of care in several settings [7,44,45], suggest that it is essential to increase efforts to implement evaluation processes that reflect the healthcare quality based on current evidence and related practice guidelines. The application of the JCAHO PC indicators has demonstrated to be feasible, intuitive and useful to measure perinatal hospital performance, and, although the poor comparability among multiple available quality measures represents a barrier, these performance metrics can be reliably used within an institution, thus enabling comparisons of performance over time, particularly after the implementation of quality improvement interventions.…”
Section: Discussionsupporting
confidence: 88%
“…The quality of care provided to the adult hospitalized Italian population has been scrutinized in the past years by use of adequate indicators [7,8], whereas only sparse data is available for perinatal care, although an interesting approach suggesting the use of a set of 19 indicators for the performance assessment in the maternity pathway in one region of Italy has thoroughly taken into account also perinatal care indicators [9]. In this context, the primary aim of this study was to assess the quality of perinatal care in a specific geographical area of Italy using the JCAHO indicators, since, compared with PNE indicators, they involve more aspects of perinatal care and include indicators for which there is no standardized monitoring system in Italy, such as breastfeeding or elective delivery [10].…”
Section: Introductionmentioning
confidence: 99%
“…The percentage of patients prescribed beta blockers at arrival was suboptimal and lower than observed in some other studies (65-83%) [40][41][42]. Multivariate analysis showed that patients with STEMI (compared to UA), heart failure or female patients were less likely to receive beta blockers at arrival.…”
Section: Discussionmentioning
confidence: 55%
“…This result is a concern, as already highlighted by Toren et al, that found that only 40% of patients discharged from hospital had received counselling and that it was associated with knowledge on medications [ 24 ]; moreover Coleman et al reported that discrepancies between prescribed medication and actual old patients’ behaviour were also related to system-associated factors, such as conflicting information from different informational sources [ 25 ]. Although alarming, this finding was not surprising; in a study conducted by some of us to evaluate the adaptability of the Joint Commission on Accreditation of Healthcare Organizations (JCAHO) and the Centers for Medicare & Medicaid Services (CMS) quality indicators in our geographical area we found that rates regarding adherence to discharge instructions in heart failure patients, that is one of the patient safety indicators, was “noticeably intangible” [ 26 ], thus confirming low attention to counseling at discharge in our hospitals. The investigation of quality and extent of information provided to patients showed that counselling at discharge performed by hospital physicians on new prescribed therapies dealt mainly on the rationale, dosing, route and timing of medications administration, whereas potential problems and/or actions to take in presence of errors or side effects of medications were not discussed at discharge.…”
Section: Discussionmentioning
confidence: 99%